2023
DOI: 10.1002/ptr.8050
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive exploration of Biochanin A as an oncotherapeutics potential in the treatment of multivarious cancers with molecular insights

Md Sohel

Abstract: Cancer is considered a leading cause of mortality. This rising cancer death rate and several existing limitations like side effects, poor efficacies, and high cost of the present chemotherapeutic agents have increased the demand for more potent and alternative cancer treatments. This review elucidated a brief overview of Biochanin A (BCA) and its potentiality on various cancers with details of anticancer mechanism. According to our review, a number of studies including in silico, in vitro, pre‐clinical, and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…In silico approaches were used to conduct pharmacokinetics or ADME/Tox prediction through computational tools such as Schrodinger's QuickPro modules, online accessible server admetSAR, and SwissADME. 4,120 It was observed that molecular weight, QPlogPo/w, HBD, and HBA of calycosin were 284.26 g/mol, 1.5, 2, and 5, respectively, indicating good drug-likeness properties of the compounds. Molecular weight (MW), volume, density, nHA, nHD, nRot, nRing, MaxRing, nHet, fChar, nRig, flexibility, stereo centers, TPSA, logS, logP, and logD were among the physicochemical characteristics radar of calycosin that were computed using the ADMETlab 2.0 software and were shown in Figure 6.…”
Section: Pharm Aco Kin Etics Of Calycosin and Future Perspective In D...mentioning
confidence: 99%
See 1 more Smart Citation
“…In silico approaches were used to conduct pharmacokinetics or ADME/Tox prediction through computational tools such as Schrodinger's QuickPro modules, online accessible server admetSAR, and SwissADME. 4,120 It was observed that molecular weight, QPlogPo/w, HBD, and HBA of calycosin were 284.26 g/mol, 1.5, 2, and 5, respectively, indicating good drug-likeness properties of the compounds. Molecular weight (MW), volume, density, nHA, nHD, nRot, nRing, MaxRing, nHet, fChar, nRig, flexibility, stereo centers, TPSA, logS, logP, and logD were among the physicochemical characteristics radar of calycosin that were computed using the ADMETlab 2.0 software and were shown in Figure 6.…”
Section: Pharm Aco Kin Etics Of Calycosin and Future Perspective In D...mentioning
confidence: 99%
“…In silico approaches were used to conduct pharmacokinetics or ADME/Tox prediction through computational tools such as Schrodinger's QuickPro modules, online accessible server admetSAR, and SwissADME 4,120 . It was observed that molecular weight, QPlogPo/w, HBD, and HBA of calycosin were 284.26 g/mol, 1.5, 2, and 5, respectively, indicating good drug‐likeness properties of the compounds.…”
Section: Pharmacokinetics Of Calycosin and Future Perspective In Drug...mentioning
confidence: 99%
“…In the context of colorectal cancer, the development of resistance mechanisms can compromise the effectiveness of targeted therapies, limiting their long-term efficacy. Understanding the molecular basis of drug resistance is essential for devising strategies to overcome or prevent it, ensuring the sustained success of precision medicine interventions. , …”
Section: Challenges and Considerations In Precision Medicine Implemen...mentioning
confidence: 99%
“…Understanding the molecular basis of drug resistance is essential for devising strategies to overcome or prevent it, ensuring the sustained success of precision medicine interventions. 174,175 Another critical consideration in precision medicine against colorectal cancer is drug specificity. While targeted therapies aim to selectively inhibit specific molecular pathways involved in cancer progression, achieving sufficient specificity presents a significant challenge.…”
Section: Integration Of Biomarkermentioning
confidence: 99%
“…Enhancing its bioavailability and reducing the total amount are crucial strategies to maximize its effectiveness in cancer treatment. Some possible approaches, including formulation optimization (nanoparticle formulations and micelles and liposomes), prodrug development, combination therapy, targeted therapy, enhancing absorption, bio-enhancers, incorporating advanced drug delivery systems, and optimizing administration routes can significantly improve the bioavailability of esculetin and reduce the total dose required for effective cancer treatment, thereby minimizing potential side effects and improving patient outcomes.PHARMACOKINETICS OF ESCULETIN AND FUTURE PERSPECTIVE IN DRUG DEVELOPMENTIn silico approaches conducted pharmacokinetics or ADME/Tox prediction through computational tools such as Schrodinger's QuickPro modules, online accessible server admetSAR, and SwissADME were used 114. Using Lipinski's "Rule of Five," the "drug-likeness" test was conducted, and all found compounds passed the test.…”
mentioning
confidence: 99%